The Right to Self-Determination of Kurds in Iraq; Perspectives International Law - Abdulkareem Fendi, Pasar; Mat Basir, Salawati; Abdulkarim Findi, Hakar; Othman Rahman, Hazhar (International Journal of Psychosocial Rehabilitation, 2020)
The principle of self-determination has come a long way from its origins as a tool for political rhetoric to its current status as a right of international law valid erga omnes. However, the contents of the right to self-determination, as well as its applicability, remain unclear. This holds true especially concerning national minorities, which have not traditionally been considered recipients of this right. This paper investigates the extent to which national—particularly ethnic—minorities have a legal right to self-determination, both internally within a state and externally, allowing for secession and the formation of a new state. However, it discusses the meaning of the right to self-determination in its historical and contemporary perspective and examines the different options available for the accommodation of contested self-determination claims. Detailing these implications in relation to the Iraqi Kurdistan Region (IKR).